Fufang Xueshuantong alleviates diabetic retinopathy by activating the PPAR signalling pathway and complement and coagulation cascades. (30th January 2021) - Sun, Hui-hui; Chai, Xin-lou; Li, Hong-li; Tian, Jing-yun; Jiang, Kun-xiu; Song, Xing-zhuo; Wang, Xi-rui; Fang, Yong-sheng; Ji, Qingxuan; Liu, Hanying; Hao, Gai-mei; Wang, Wei; et al.
Abstract: Ethnopharmacological relevance: Fufang Xueshuantong (FXST) is a traditional Chinese patent medicine composed of Panax notoginseng (Burkill) F.H.Chen ( Araliaceae ), Salvia miltiorrhiza Bunge ( Lamiaceae ), Astragalus propinquus Schischkin ( Leguminosae ), and Scrophularia ningpoensis Hemsl. ( Scrophulariaceae ). It has been widely used for the treatment of diabetic retinopathy (DR) and exerts a positive clinical therapeutic effect. Aim of the study: The aim of this study was to observe the effect of FXST on diabetic rat retinas and investigate its pharmacological mechanism for improving DR. Methods: The diabetic rat model was established by intraperitoneal injection of streptozotocin. The rats were divided into a normal group, diabetic group, and FXST group. The rats in the FXST group were treated with FXST by intragastric administration for 12 weeks while other rats were given the same volume of normal saline. The haemodynamic parameters of the central retinal artery in the rats were measured by ultrasound. Haematoxylin-eosin staining was utilised to observe the pathological structural changes in the retina. The apoptosis of retinal nerve cells was detected by terminal deoxynucleotidyl transferase dUTP nick end labelling. RNA sequencing was used to screen the differentially expressed genes (DEGs), and enrichment analyses were performed. The DEGs were validated through real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR). Results: The peak systolic velocity, end diastolic velocity, and mean velocity decreased while the resistance index and pulsatility index increased in the diabetic rat retinas. FXST also improved haemodynamics. In contrast with the diabetic group, FXST allayed the disorder and oedema of the retinal structure in addition to reversing the reductions in retinal thickness and retinal ganglion cell number. It also decreased the apoptosis index of retinal cells. A total of 1134 DEGs were identified by RNA sequencing in the FXST group compared to the diabetic group, including 814 upregulated genes and 320 downregulated genes. These genes were enriched in the complement and coagulation cascades as well as the peroxisome proliferator-activated receptor (PPAR) signalling pathway. Several DEGs, including PPAR gamma, perilipin 4, acyl-CoA dehydrogenase long chain, CD55 molecule, and plasminogen activator urokinase, were identified by qRT-PCR, and the results were consistent with the RNA sequencing data. Conclusions: FXST alleviates DR by improving the haemodynamics and morphological alterations of diabetic rat retinas, which are mediated by complement and coagulation cascades and the PPAR signalling pathway. Graphical abstract: Image 1